The Effect of Doom Scrolling and Digital Advertising on Purchase Decisions Through Impulsive Buying, with Self-Control as a Moderating Variable Among Social Media Users - Naila Putri Salafina; Muchammad Shocibul Munir; Moh Anta Sifau Fuadi; Makhdum Al Thaqolaini; Muhammad Fadil Khosyi’in; Sinollah (Marcha Institute, 2026)
This study aims to analyze the effect of doom scrolling and digital advertising on purchase decisions mediated by impulsive buying, and to examine the moderating role of self-control among social media users. A quantitative approach with a survey design was employed. Data were collected using a structured Likert-scale questionnaire (1–5) distributed to 105 respondents selected via purposive sampling. Data analysis involved multiple regression, Baron and Kenny mediation testing, and moderated multiple regression (MMR) with interaction terms. Results indicate: (1) doom scrolling positively and significantly affects impulsive buying (β = 0.341; p < 0.001); (2) digital advertising positively and significantly affects impulsive buying (β = 0.284; p < 0.001); (3) impulsive buying positively and significantly affects purchase decisions (β = 0.483; p < 0.001); (4) impulsive buying fully mediates the relationship between doom scrolling and purchase decisions; (5) impulsive buying partially mediates the relationship between digital advertising and purchase decisions; and (6) self-control negatively and significantly moderates the effect of impulsive buying on purchase decisions (B = -0.043; p = 0.026). These findings offer theoretical and managerial implications for digital marketing practitioners and consumers in the social media economy era.